Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Ax² + bx +c = 0

rewrite as x² + b/a x + c/a = 0 call - b/a = b' c/a = c'

x² - b' x + c' = 0 equaiton 1

IF α and β are the roots,

(x - α) (x - β) = 0 expand this expression then, we get

x² - (α+ β) x +αβ = 0 comparew with the equation 1

α+β = b' abd αβ = product

If some trial values fail, use the formula

Δ = √b² - 4ac and α, β = (-b +- Δ)/2

Often trying simple values of x as x=1, -1, -2, -3, 2, 3 could give a root directly.

rewrite as x² + b/a x + c/a = 0 call - b/a = b' c/a = c'

x² - b' x + c' = 0 equaiton 1

IF α and β are the roots,

(x - α) (x - β) = 0 expand this expression then, we get

x² - (α+ β) x +αβ = 0 comparew with the equation 1

α+β = b' abd αβ = product

**Convert the equation in the form of equation 1 and then try to factor the c' so that the sum of the factors becomes minus of coefficient of x.**If some trial values fail, use the formula

Δ = √b² - 4ac and α, β = (-b +- Δ)/2

Often trying simple values of x as x=1, -1, -2, -3, 2, 3 could give a root directly.

product = alfa x beta

alfa+ beta= -b/a and alfa x beta= c/a where ax^2+bx+c is any quadratic.